Analisis Tagline Merek yang Mengandung Unsur Pornografi di Media Sosial - Inda Nurdahniar (Universitas Batanghari Jambi, 2021)
Brands have economic value so protection is needed. Brand protection arises when registered. But this is excluded against brands that contain elements of decency. In reality many businesses use brands with the word, logo plus taglines that contain pornographic elements. The problem is seen if the brand continues to operate in the middle of society and even penetrated into social media. Based on the results of the study, the arrangement of brand taglines containing pornographic elements on social media is not specifically regulated but spread across various laws and regulations and there is overlapping. In fact the @ngocok.eskopi account with the trademark